Rediscovery of Gonostegia Pentandra (Roxb.) Miq. (Urticaceae) from Bangladesh Sundarban (Jahangirnagar University Journal of Biological Sciences, 2018)
Abstract not availableJahangirnagar University J. Biol. Sci. 7(2): 115-119, 2018 (December)